Radioligand therapy of metastatic prostate cancer using (177)Lu-PSMA-617 after radiation exposure to (223)Ra-dichloride - Ahmadzadehfar, Hojjat (Oncotarget, 2017)
Radioligand therapy with (177)Lu-PSMA-617 is an innovative and effective therapy for castrate-resistant metastatic prostate cancer patients. For patients with symptomatic bone metastases without visceral metastases, the guidelines recommend radionuclide therapy with (223)Ra-dichloride as a single therapeutic agent or in combination with hormone therapy. The aim of this study was to evaluate the safety of repeated cycles of (177)Lu-PSMA-617 after exposure to more cycles of (223)Ra. Forty-nine patients were treated with three cycles of Lu-PSMA-617 divided into two groups subjected to a history of therapy with (223)Ra. Group 1 included 20 patients, who had received therapy with (223)Ra prior to Lu-PSMA-617 therapy. Group 2, which was the control group regarding hematotoxicity, comprised 29 patients without any history of a bone-targeted radionuclide therapy. No CTC 4° hematotoxicity was observed in the entire study population. There was no CTC 3° or CTC 4° leucopenia in either group. One and three patients from group 1 and 2, respectively, showed CTC 3° anemia. In group 1 there was significantly more CTC 2° anemia (50% vs. 6.9%) (p=0.008). One patient from group 1 (5%) showed a CTC 3° thrombocytopenia without any concurrent anemia, and two patients from group 2 (7%) showed a CTC 3° thrombocytopenia, one with CTC 3° anemia and one without any anemia. There were no significant differences between the two groups regarding leucopenia and thrombocytopenia. These results confirmed that performing repeated cycles of Lu-PSMA-617 after (223)Ra seems to be safe with a very small probability of hematotoxicity.